Bioconversion of Platycodon Grandiflorum Saponins by the Platycodin D‐Converting Microorganism, Yeast Cyberlindnera Fabianii. Issue 3 (23rd November 2015) - Lee, Nam Keun; Nyakudya, Elijah; Jeong, Yong‐Seob
Abstract: This study sought to identify a new strain of microorganism from a natural source, nuruk, for use in the production of platycodin D (PD) from the roots of P latycodon grandiflorum (PG). A non‐ S accharomyces yeast capable of producing PD was isolated from nuruk and identified as C yberlindnera fabianii . The enzyme responsible for PD production was traced with partially purified crude enzyme extracts (CEE) from yeast C . fabianii 48. The best enzyme fraction responsible for production of PD was the >100 kDa CEE. In addition, the bioconversion pathway for production of PD by the >100 kDa CEE with PD, platycodin D2 (PD2) and platycodin D3 (PD3) substrates was investigated. The >100 kDa CEE was able to degrade PD3 to PD and had no effect on PD and PD2. Practical Applications: Platycodin D, the most superior saponin in P latycodon grandiflorum (PG), has been reported to have numerous biological effects including prevention and treatment of hyperlipidemia, obesity, inflammation and cancer. This study will contribute to future research in drug development, health benefits and applications by searching for potent fermenting microorganisms and developing an improved bioprocess for use in large‐scale production of value‐added PG saponins.